Preparation and scintillation properties of LGSO:Ce crystals - Sidletskiy, O.Ts.; Bondar, V.G.; Grinyov, B.V.; Kurtsev, D.A.; Baumer, V.N.; Belikov, K.N.; Shtitelman, Z.V.; Tkachenko, S.A.; Zelenskaya, O.V.; Starzhinsky, N.G.; Katrunov, K.A.; Tarasov, V.A. (Functional Materials, 2009)
Lu₂ₓGd₂₋₂ₓSlO₅:Ce single crystals with different Lu/(Lu+Gd) atomic ratio have been obtained by the Czochralski technique. It has been shown that the polymorph transition P2₁/c-C2/c space symmetry at substitution of Gd atoms by Lu takes place at Lu/(Lu + Gd) = 0.1-0.2. The obtained crystals with C2/c symmetry type demonstrate good scintillation characteristics. High Ce³⁺ segregation coefficient together with preferred inclusion of cerium into the seven-fold oxygen - coordinated position provide high light yield and good energy resolution of the crystals.